The Importance of Structuring Relationships Between Local Governments and Business Entities in The Perspective of State Administrative Law in Batam City, Riau Islands - Indra, Mexsasai; Fauzan, Fadhilah (Magister of Law, Faculty of Law, University of Mataram, 2023)
This article explains the importance of structuring the relationship between local government and local business entities from the perspective of state administrative law in Batam City, Riau Archipelago. This study used a qualitative research method, in which several relevant sources obtained were analyzed using descriptive analysis to be able to explain and answer the research questions as a whole. The findings of this study indicate that the dynamics of the dualism of authority that occurs between the Batam City Government and the Batam Concession Agency have violated several principles of good governance, namely those relating to the principle of legal certainty, the principle of not mixing authority, and the principle of implementing the public interest. In the process, to overcome the dualism of authority that occurs, it is necessary to integrate the Free Trade Areas (FTA) of Batam, Bintan, and Karimun with the Free Port Concession Agency (FPCA) by placing the authority of the FPCA under the control of the Governor of the Riau Archipelago Province. Therefore, to adopt a better possibility of the findings of this study, it is very important to immediately amend Government Regulation Number 46 of 2007 concerning the Free Trade Zone and Free Harbor of Batam as amended several times, most recently by Government Regulation Number 62 of 2019 concerning the Second Amendment on Government Regulation Number 46 of 2007 concerning Free Trade Zones and Free Ports.